Using vortex generators for flow separation control on tidal turbine profiles and blades. (March 2023) - Manolesos, M.; Chng, L.; Kaufmann, N.; Ouro, P.; Ntouras, D.; Papadakis, G.
Abstract: Tidal energy can play an important role in the Net Zero transition. Increasing tidal turbine performance through innovation is crucial if the cost of tidal energy is to become competitive compared to other sources of energy. The present investigation is a proof-of-concept study for the application of Vortex Generators (VGs) on tidal turbines in view of increasing their performance. The more mature wind energy industry uses passive VGs either as a retrofit or in the blade design process to reduce separation at the inboard part of wind turbine blades. Tidal turbine blades also experience flow separation and here we examine whether passive vane VGs can be used to reduce or suppress that separated flow. First, a wind tunnel investigation is performed to assess the performance of VGs on a 20% thick profile from the blade. Then, the VG effect on the 2D-profile is modelled in a Reynolds Averaged Navier-Stokes in-house solver. Results show that low profile VGs, i.e. VGs shorter than the local boundary layer, can increase the performance of the blade profile and successfully reduce flow separation. The VG effect on blade performance is examined in model scale and in full-size. VGs successfully suppress separation in both cases and it is shown that full-size information should be used for the placement of VGs. A maximum power coefficient increase of 1.05% is observed at a tip speed ratio of λ = 3 . The present proof-of-concept study demonstrates for the first time the potential of passive VGs to be included either in the design process of a tidal turbine blade or as a retrofit solution.